ANALISIS TANGGUNG JAWAB HUKUM TERHADAP TINDAK PIDANA MANIPULASI PASAR DAN PERLINDUNGAN HUKUM BAGI INVESTOR MINORITAS STUDI KASUS:POSA - Septiana, Hasna Kharimah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This article aims to analyze the legal protection for investors is related to the practice of market manipulation as regulated in Law Number 8 of 1995 concerning the Capital Market and what forms of legal protection are provided by the Financial Services Authority (OJK), Indonesia Stock Exchange (BEI), KSEI and KPEI as well as the impact of market manipulation and how the accountability will be imposed on the actors.This article uses a normative juridical legal research method. The normative juridical character is carried out by examining secondary data or by the method of literature study of legal materials which are the reference for research, which is focused on examining the application of rules or norms in positive law. The research was carried out by means of a literature study of the laws and regulations related to market manipulation in the capital market sector.The case study in this research is the alleged case of market manipulation conducted by PT Bliss Property Indonesia Tbk (POSA) which occurred on May 10th, 2019, allegedly taking action to manipulate the market so that there are drastic fluctuations in the movement of stock prices out of the ordinary and without accompanied by clear fundamentals of the company, it is suspected that this trade is not fair so that it harms one of the investors